Elevated Levels of Sialic Acid and Lipid-Associated Sialic Acid in Plasma of Rheumatoid Arthritis Patients - Hamad, N. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The objective of this study is to evaluate plasma levels of total Sialic acid TSA and Lipid â€“associated Sialic acid LSA as a marker of Rheumatoid Arthritis AR. Plasma Sialic acid is known as a parameter of inflammation. In the present study, in order to explore the potential role of sialic acid in arthritis rheumatoid, plasma sialic acid levels, plasma LSA and total protein in patients with arthritis rheumatoid were measured. A total 40 patients were compared with 40 healthy control subjects. Plasma TSA, LSA and TP level were determined spectrophotometrically in plasma samples. Plasma Sialic acid levels were significantly increased in RA (88.48Â±14.15 mg/dl, P